Tecendo a moda: a presença de jovens nas facções das indústrias de confecção em Divinópolis - Barreto, Joanice Maria (2016)
This is a study about the presence of young people in subcontracting of sewing services of clothing industries' located in the municipality of Divinópolis, Minas Gerais. These subcontracting of sewing services are usually installed in general households. In the survey, respondents were six young men and women aged between 17 and 24, running activities related to that city's apparel sector. The place of residence also becomes a salaried workspace for those young people who venture into the uncertainties of wage earning labor. Like this, they are integrated into the market and earn money to minimally meet their personal needs. However, these young people do not consider what they do precarious or passing. From their point of view, the tasks they perform in the subcontracting of sewing services are important for clothing Industries, being a source of income for them. It was also possible with this research to know these young respondents choices, personal relations and consuming demands